Dobutamine-induced hyperaemia inversely correlates with coronary artery stenosis severity and highlights dissociation between myocardial blood flow and oxygen consumption. Issue 9 (17th March 2006) - Jagathesan, R; Barnes, E; Rosen, S D; Foale, R; Camici, P G
Abstract : Objectives: To compare the relationship between dobutamine myocardial blood flow (MBF), rate–pressure product (RPP) and stenosis severity in patients with coronary artery disease (CAD). Methods: 27 patients with single-vessel CAD were allocated to three groups based on stenosis severity: group 1, 50–69% (n = 9); group 2, 70–89% (n = 9); and group 3, ⩾ 90% (n = 9). Nine normal volunteers served as controls. Resting and dobutamine MBF were measured by positron emission tomography in the territory subtended by the stenosis (Isc) and remote myocardium (Rem). Mean left ventricular MBF was used for controls. Results: In group 1, mean dobutamine MBF-Isc (2.48 (SD 0.48 ml/min/g)) and dobutamine MBF-Rem (2.70 (0.50) ml/min/g, NS) were comparable. In groups 2 and 3, dobutamine MBF-Isc (1.91 (0.44) and 1.22 (0.21) ml/min/g) was significantly lower than dobutamine MBF-Rem (2.27 (0.28) and 1.98 (0.25) ml/min/g, p < 0.02 and p < 0.005, respectively). An inverse relation between dobutamine MBF and stenosis severity existed both in Isc (r = 0.79, p < 0.001) and in Rem territories (r = 0.71, p < 0.001). For any given RPP, dobutamine MBF was greater in controls than in Rem (p < 0.05), which in turn was greater than in Isc (p < 0.05). Conclusion: Dobutamine MBF inversely correlated with stenosis severity and achieved significant flow heterogeneity for coronary stenoses > 70%. Dobutamine MBF and RPP were dissociated in both Isc and Rem segments in patients compared with controls.